Combined Treatment With Dichloroacetic Acid and Pyruvate Reduces Hippocampal Neuronal Death After Transient Cerebral Ischemia - Hong, Dae Ki; Kho, A Ra; Choi, Bo Young; Lee, Song Hee; Jeong, Jeong Hyun; Lee, Sang Hwon; Park, Kyoung-Ha; Park, Jae-Bong; Suh, Sang Won (Frontiers in Neurology, 2018)
Transient cerebral ischemia (TCI) occurs when blood flow to the brain is ceased or dramatically reduced. TCI causes energy depletion and oxidative stress, which leads to neuronal death and cognitive impairment. Dichloroacetic acid (DCA) acts as an inhibitor of pyruvate dehydrogenase kinase (PDK). Additionally, DCA is known to increase mitochondrial pyruvate uptake and promotes glucose oxidation during glycolysis, thus enhancing pyruvate dehydrogenase (PDH) activity. In this study, we investigated whether the inhibition of PDK activity by DCA, which increases the rate of pyruvate conversion to adenosine triphosphate (ATP), prevents ischemia-induced neuronal death. We used a rat model of TCI, which was induced by common carotid artery occlusion (CCAO) and hypovolemia for seven minutes while monitoring the electroencephalography (EEG) for sustained isoelectric potential. Male Sprague-Dawley rats were given an intraperitoneal injection of DCA (100 mg/kg) with pyruvate (50 mg/kg) once per day for two days after insult. The vehicle, DCA only or pyruvate only-treated rats were injected on the same schedule. Our study demonstrated that the combined administration of DCA with pyruvate significantly decreased neuronal death, oxidative stress, microglia activation when compared with DCA or pyruvate injection alone. These findings suggest that the administration of DCA with pyruvate may enhance essential metabolic processes, which in turn promotes the regenerative capacity of the post-ischemic brain.